Técnicas y juegos de relajación para afrontar el estrés académico en los estudiantes de segundo año de bachillerato “b” de la unidad educativa Pio Jaramillo Alvarado, Loja, 2017-2018. - Imaicela Roa, Lucia Matilde (2018)
The academic requirements in the process of basic education training generate certain degrees of dissatisfaction, fatigue and apathy, which affects their academic performance, in front of this problem arises the subject of thesis: TECHNIQUES AND RELAXATION GAMES TO FACE THE ACADEMIC STRESS IN THE STUDENTS OF SECOND YEAR OF BACHILLERATO B, OF THE EDUCATIONAL UNIT PIO JARAMILLO ALVARADO, LOJA. 2017-2018; aims to address academic stress through relaxation techniques and games; Descriptive study, cross-sectional and pre-experimental design, the methods used: the analytical-synthetic, deductive-inductive and statistical. The SISCO Inventory of academic stress was applied in a sample of 15 students. The results (Pre-test) 47% manifest the academic stressor more often is the evaluation of teachers at a deep and moderate level, 27% state that the academic stressor is the type of work that teachers ask at a level purple, likewise 27% state that participation in classes for them is an academic stressor at a moderate level. It is concluded that the researched population manifests in considerable percentages in moderate levels the academic stressors: evaluations of the professors, the type of work that the professors ask for and the participation in class; and that after the application of the proposal techniques and relaxation games to confront academic stress, it is validated as excellent that raises knowledge that allows facing stress.